Investigation of parenteral drug use in family health care centers across 32 provinces of Turkey [Türkiye'ni̇n 32 i̇li̇ndeki̇ ai̇le saǧliǧi merkezleri̇nde parenteral i̇laç kullaniminin araştirilmasi] - (:unkn) unknown (My University, 2013)
Irrational use of parenteral drugs (PD) causes several healthcare problems throughout the world. In this study, it was aimed to investigate the PD use by analyzing the prescriptions including PD written by family physicians practicing in different provinces of Turkey. Total of 2 428 246 prescriptions including PD, which were entered via "Family Medicine Information System" into electronic database by physicians practicing in 32 provinces of Turkey during 2010, were analyzed by some drug use indicators. Diclofenac was the most frequently prescribed PD and 25.2% of the prescriptions included parenteral analgesics. The most frequently prescribed PD showed differences by provinces and months. Number of parenteral prescriptions per 10 000 inhabitants was highest in Barti{dotless}n (2679), Denizli (2220) and Burdur (1847). Number of PD showed differences by months and October had the highest number (10.9%). Although, some discussions related to PD use may occasionally occur in Turkey, this is the first study that takes this topic in detail. Considering the high sample size, important findings related to PD use were revealed with this study. Accordingly, PD use showed differences by provinces and months. These findings are expected to guide for attempts regarding PD use.
Keywords: Parenteral drug; Physician; Prescription